Website-Based E-Pharmacy Application Development to Improve Sales Services Using Waterfall Method - Suhirman Suhirman; Ahmad Tri Hidayat; Wahyu Adjie Saputra; Shoffan Saifullah (International Journal of Advances in Data and Information Systems, 2021)
An online shop is a way of trading and shopping online via the internet. Online sales in the business sector will significantly help reduce operational costs, especially for customer activities; in its contribution to commerce, online sales can also increase selling power and widely facilitate the marketing of a product. “Seger Waras” Pharmacy is an agency engaged in the business of selling medicines and medical equipment. “Seger Waras” Pharmacy requires an online sales website or online store, which is intended to maximize service to existing or new customers. Therefore, the authors conducted research on the design of the e-pharmacy application, which is a web-based medicine sales system at the Seger Waras Pharmacy. This study aims to increase the revenue of the relevant agencies and provide complete information about drug use to customers. Data collection methods use observation and interview methods for system models using Data Flow Diagrams, Entity Relationship Diagrams, and Context Diagrams. The software used by MySQL as a database server, Apache as a web server, Sublime Text 3 for writing PHP and HTML programming languages, and Bootstrap as a framework. The result of the system that has been completed is an online store application that makes it possible to sell and purchase drugs online; the online shop at the “Seger Waras” Pharmacy can increase sales turnover and promote business.